Perancangan Sistem Informasi Untuk Perawatan Dan Perbaikan Modul Pratikum Berbasis Web - Anggara Nasution; Raemon Syaljumairi; Rusfandi rusfandi (Teknik Elektro Politeknik Negeri Padang, 2018)
Microprocessor and microcontroller laboratories are type III laboratories that are in the electronics engineering study program majoring in electrical engineering, this laboratory serves the activities of student practices for microprocessor system courses, microcontroller systems and interfaces I and II and very large scale intergration (VLSI) programmable logic devices and programmable electronics. Laboran as manager and person in charge of the laboratory, every month submits reports on equipment support facilities and practice modules made manually to the head of the laboratory. Every day the laboratory staff must examine all equipment activities one by one such as computers and practice modules to find out the latest conditions. Seeing the problems above, we need a system solution that can provide fast, accurate, complete and integrated information as a whole. The purpose of this study is to produce an information system design for maintenance and repairs to microprocessor and microcontroller laboratories. The method used in this study analyzes the current system to create a conceptual model so as to produce a database diagram. Next, the design of the display includes the design of the application interface such as the reporter display, laboratory performance reports etc. To further maximize laboratory use and quality teaching and learning is expected that students, lecturers and staff will also participate by reporting damage to supporting facilities at the microprocessor and microcontroller laboratory.